Short-term changes of response indicators of ecosystem status in broadleaved forests in Tuscany (central Italy) - Ferretti, M; Bonini, I; Bussotti, F; Celesti, C; Cenni, E; Chiarucci, A; Cozzi, A; De Dominicis, V; Grossoni, P; Leonzio, C (WATER AIR AND SOIL POLLUTION, 1999)
The status of different response indicators of forest condition were measured and assessed between 1995 and 1997 at 6 Permanent Monitoring Plots (PMPs) in Tuscany (central Italy), where beech, holm oak and Turkey oak are the most frequent tree species. Foliage transparency, leaf damage and crown dieback have changed significantly over the monitoring period. Leaf area, length of the current year shoots, and total leaf area changed as well, but only for Turkey oak. Changes were consistent between and within the plots. Different indices of plant diversity showed marked changes, apparently linked to natural dynamics within individual ecosystems. These rapid and contrasting fluctuations in the various indicators of forest ecosystem make it difficult to derive a synthesis about the general condition of ecosystems and - especially - about the effects of air pollution.
Keywords: Biodiversity; crown condition; crown productivity; forest health; long-term monitoring; Permanent plots; response indicators

New types of damage to forest trees typical of the Mediterranean region - Clauser, F; GELLINI, R; Bussotti, F; Cenni, E; Bottacci, A (European Journal of Forest Pathology, 1989)
Since 1984 a new type of damage to the typical tree species growing in the mediterranean area has been observed. The pathological picture includes the typical features of “Waldsterben”. The new symptoms occurring in Pinus pinea, P. pinaster, P. halepensis and Quercus ilex are described.
Keywords: crown damage; damage; decline (voyant); foliage reduction